Analisis Pengaruh E-Wallet, Pendapatan Per Kapita, dan Suku Bunga Terhadap Daya Beli Masyarakat Di Indonesia Tahun 2020-2024 Dalam Perspektif Ekonomi Islam - Mia Damayanti; Liya Ermawati; Adhe Risky Mayasari (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2026)
The purpose of this study focuses on analyzing the influence of e-wallet usage, per capita income, and interest rates on the purchasing power of Indonesians in the 2020–2024 period from an Islamic Economics perspective. This finding uses a quantitative approach based on time series data obtained from official publications of the Central Statistics Agency (BPS) and Bank Indonesia. The multiple linear regression method was used in this analysis and processed using E-Views 13 software. The research findings indicate that e-wallet usage has no significant influence on purchasing power, while per capita income has a positive and significant influence, while interest rates are known to have no significant effect on purchasing power. Thus, this finding confirms that income is the main determinant of people's purchasing power. In line with these findings, increasing purchasing power needs to be directed not only at quantitative aspects, but also at the quality of consumption behavior. From an Islamic Economics perspective, consumption must be carried out proportionally, avoiding israf, and ensuring that income and transactions are carried out in accordance with sharia principles.